Association of polycyclic aromatic hydrocarbons (PAHs) and lead co-exposure with child physical growth and development in an e-waste recycling town. (November 2015) - Xu, Xijin; Liu, Junxiao; Huang, Chaoying; Lu, Fangfang; Chiung, Yin Mei; Huo, Xia
Highlights: Higher levels of PAH and lead are found in the blood of children from Guiyu. IP is the most abundant congener among the 16 measured PAHs. Milk consumption might be a protect factor from PAH accumulation. PAH levels were negative associated with child height and chest circumference. High PAH levels in children from Guiyu comes from e-waste recycling activities. Abstract: Informal e-waste recycling activities results in serious environmental pollution of PAHs. We evaluated the body burden of 16 PAH congeners and potential health risks for children. A total of 167 children from exposed and reference area entered this study. Child blood samples were collected; height, weight, head and chest circumferences were measured. Blood PAH and lead concentrations were determined. The blood median of total PAHs from the exposed group was significantly higher than the reference group (68.53 μg/L vs. 26.92 μg/L, P  < 0.01). The major sources of Σ16-PAH and Σ7 carcinogenic-PAH were residence adjacent to e-waste workshop, paternal occupation related to e-waste recycling and house as a workshop. Inverse correlations were observed in the age and milk consumption with these two PAH groups, while a positive association was found between BMI and Σ7 carcinogenic-PAH, and between child height and blood lead. When divided into high and low exposure groups by Σ16-PAH, a significant negative association was found between body height and blood PAHs (β and 95%CI: −3.838, −6.469 to −1.206), while for weight and chest circumferences, negative associations were obtained only in the male subgroup before adjustment. After adjustment by sex, age, child milk products consumption per month and blood lead, child height was negatively associated with Σ16-PAH (β and 95%CI: −3.884, −6.736 to −1.033). Same trends were observed for child chest circumference (β and 95%CI: −1.147, −2.229 to −0.065). We suggest a negative association of PAHs and child height and chest circumference, while the correlation is more obvious in boys.